Binuclear Cu(II) Schiff base complexes as prescursors for the synthesis of CuO nanoparticles: anticancer activity against MCF-7 cell line. Issue 2 (2nd April 2016) - Moorthy, Malathy; Rangappan, Rajavel
Abstract: Homobinuclear Cu(II) complexes1 and2 were synthesized and characterized by elemental analysis, FTIR, 1 H NMR, Mass, UV–vis, magnetic moment, ESR and TGA studies. The synthesized complexes1 and2 were used as precursors for the synthesis of CuO Nps by calcination method. CuO Nps were characterized by FTIR, XRD, scanning electron microscopy (SEM), and EDX. XRD peaks clearly indicated the monoclinic structure of CuO. CuO nanoparticles were synthesized with average particle size 3–4 and 5–10 nm. The morphologies and size of the obtained products were further investigated by SEM. Presence of essential constituents of CuO Nps was investigated by EDX studies. The Anticancer activity of the precusors1 &2 and its nanoparticles have been analyzed against the MCF-7 cell line by MTT assay. The Precusor1 with IC50 value 12.66 μM was found to have high anticancer activity than other compounds. Synopsis: Binuclear Cu(II) Schiff base complexes1 &2 were synthesized from the ligandsL1 andL2, respectively. Binuclear Cu(II) complexes were successfully used as a precursor for the synthesis of CuO Nps. The ligands, precusors, and the CuO Nps were analyzed for their anticancer activity against the MCF-7 cell line. Precursor1 synthesized from the ligandL1 shows high activity than other compounds due to the presence of the heterocyclic moiety. Graphical Abstract: